Sports Orthopedics - Haag T; 3; Beck H; Korthals I; Handel M; Schneider C; 3 (Dynamic Media Sales Verlag, 2018)
Problem: Physical activity has an enormous relevance for the treatment of back pain (BP) in the clinical field. This paper givesa brief overview of the evidence of physical activity for the treatment of chronic back pain and summarizes the current approach of the German national project Medicine in Spine Exercise (MiSpEx: sensorimotor training (SMT) with perturbation).Methods: 35 literature reviews were screened for inclusion criteria concerning physical activity for the treatment of cBP. Of these, 16 systematic reviews and 2 guidelines were included following the criteria: systematic review in English, evaluating pain and disability in the context of physical activity for the treatment of back pain, published 2000-2017 and considering less than a third of RCTs without a subclassification of patients. We did not conduct a quantitative meta-analysis but a qualitative synthesis. Results: Exercise Therapy reduces pain and disability in cBP patients but there is still no evidence thatanyone specific approach isthe mostfavorable. Motor control exercises (MCE) seem to improve outcomes best, but SMT was mostly unconsidered.Conclusion: SMT further improves motor control by training the adjustment to unexpected stimuli incomplex tasks considering both: afferent and efferent workloads. Furthermore, additional perturbation may improve sensorimotor adaptations through higher demands on core stability and increase the precise stabilizing feedback in cBP patients.KEY WORDS: Exercise Therapy, Chronic Back Pain, Sensorimotor Training, Proprioception